ANALYSIS OF HEALTH SERVICE QUALITY IN PUSKESMAS SRONDOL BANYUMANIK DISTRICT, SEMARANG - Sulistyaningsih, Novi; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2019)
The conception of public service is related to how to increase the capacity and capability of the government and / or local government to carry out the service function. Puskesmas as one of the individual health service facilities is part of the health resources that are very much needed in supporting the implementation of health efforts. This research was conducted to determine the quality of health services at Srondol Health Center. To measure the quality of health services in Srondol Public Health Center using the dimensions of Tangible (Physical Appearance), Reliable (Reliability), Responsiveness, Competence, Courtesy, Credibility, Security, Access, Communication (Communication), and Understanding The Customer (Understanding) and factors that affect the quality of service. The method used is descriptive quantitative, the unit of analysis in this study is individuals. Techniques for collecting data through questionnaires and direct surveys to obtain the data needed about how the quality of health services in the Puskesmas. Research Results on the quality of health services in Srondol Health Center at the General Medical Center the average level of performance is 2.99 and the level of importance is 3.37, the services of the Mother and Child Health Center with an average level of performance of 3.19 and the average level of interest 3.36 and Dental Care Center with an average performance level of 3.00 and the average level of importance is 3.31. Based on the Total Elements of Performance Levels and Interests of Srondol Health Center Health Services, it can be concluded that the average level of performance and level of importance of health services in Srondol Health Center can be said to be good, with an average performance rate of 3.05 and an average level of interest of 3 19 so that overall health services at Srondol Health Center are considered good. There are two factors that influence the quality of health services in Srondol Health Center, namely system factors and ability factors.